Magnitude determination of stars in the open cluster M46 using clear and green filters / Marnila Che Noh - Che Noh, Marnila (2006)
An open star cluster is a group of up to a few thousand stars that were formed the same giant molecular cloud, and is still gravitationally bound to each other. Open star clusters are also occasionally referred to as galactic cluster because they are almost exclusively found in the plane of Milky Way. There are two methods of measuring stars brightness namely; the aperture photometry and the point spread function. To determine the brightness of the star's in this research, the method of aperture photometry were used. The aperture photometry is a method of CCD photometry for determining the star's brightness with the use of three digital annulus to measure the brightness of the star. The scale use to represent the star's brightness is magnitude. This research is done with the objective of to image an open star cluster using CCD camera, to calculate and compare the instrumental magnitude of the stars in the cluster using two filters; green filter and clear filter. M46 is the open star clusters used in this research. The instrumental magnitude of stars using clear filter are smaller than the magnitude of stars using green filter. From the value of the magnitude of the stars, the image of stars using the clear filter is brighter than the image using green filter. As a conclusion, the green magnitude is increase when the overall magnitude increases.